2024
DOI: 10.1088/1758-5090/ad2536
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of biomimetic undulating microtopography at the dermal-epidermal junction and its effects on the growth and differentiation of epidermal cells

Chuang Gao,
Chunxiang Lu,
Huazhen Liu
et al.

Abstract: The undulating microtopography located at the junction of the dermis and epidermis of the native skin is called rete ridges (RRs), which plays an important role in enhancing keratinocyte function, improving skin structure and stability, and providing three-dimensional (3D) microenvironment for skin cells. Despite some progress in recent years, most currently designed and manufactured tissue-engineered skin models still cannot replicate the RRs, resulting in a lack of biological signals in the manufactured skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Biological experiments such as histological and immunofluorescence testing were performed on the microstructural skin model after a period of air-liquid interface culture. The results showed that the rete ridge structure played a positive role in cell proliferation, viability, and differentiation [29]. However, extrusion-based 3D printing still makes it difficult to directly shape microstructures with a certain curvature.…”
Section: Of 18mentioning
confidence: 99%
“…Biological experiments such as histological and immunofluorescence testing were performed on the microstructural skin model after a period of air-liquid interface culture. The results showed that the rete ridge structure played a positive role in cell proliferation, viability, and differentiation [29]. However, extrusion-based 3D printing still makes it difficult to directly shape microstructures with a certain curvature.…”
Section: Of 18mentioning
confidence: 99%
“…Microfluidic systems have been utilized in cell culture more frequently in recent years 17 – 20 , particularly in dynamic cell culture systems that imitate the intricate movements of bodily organs 21 24 . Microfluidic devices allow human manipulation to mimic intricate movements and possess precise dimensions that simplify the process of structural design.…”
Section: Introductionmentioning
confidence: 99%